Development of guitar parts specification advisory system using data matching technique / Khairuzzamri Yahya - Yahya, Khairuzzamri (Faculty of Computer and Mathematical Sciences, 2007)
Advisory system is an application system that helps the user in certain expertise to make choice that suitable to their preferences or needs. The system provides a recommendation, prediction or opinion that can assist the user in computerized solution. In the era of e-commerce, applying the advisory system will help increasing the business potential and also revenue, as the system can become a service that will attract the user. The system is also seem to be useful in aiding guitar players to get the most suitable guitar parts that match with their music preferences and playing styles by suggesting which parts should be used or included in their guitar. For beginner guitar player or who just recently grow interest in guitar, it is quite difficult for them to get the right or suitable guitar parts that really suits their music preferences or their way of playing guitar. The system has two recommendation modes which each method has their own target user. The first mode is specially designed for beginner guitar player who do not have even slight of idea about guitar or guitar parts. This mode require the user to input three information, their budget, their music preferences and any brand that their specifically want. The other recommendation mode is for beginner player that have brief or little experience vwth the instrument. They just have to browse the list of guitar parts and choose wliich that they like. With this, the user can get a suggestion and use that as guidance in buying their guitar parts. As a conclusion, this system will be helpfiil to beginner guitar player in buying the guitar parts that will suit well with their preferences.